Research Progress in Diseases Caused by STAT1 Gain-of-Function Mutations - LI Linpeng; MA Jing; GU Hao; SHU Zhou; MAO Huawei (罕见病研究)
Signal transduction and activator of transcription factor 1(STAT1), one of the important members of the STAT family, is a key cytoplasmic transcription factor and an important component of the JAK-STAT signaling pathway. Gain-of-function mutations in STAT1 (STAT1-GOF) impaired the dephosphorylation of STAT1 protein, mediated the enhancement of cell signaling pathways such as type Ⅰ, Ⅱ, and Ⅲ interferon(IFN) and interleukins-27 (IL-27), IL-6, IL-10, and IL-17, and inhibited Th17 cells. The clinical manifestations of STAT1-GOF are diverse, including chronic mucocutaneous candidiasis and autoimmune diseases. For the treatment of STAT1-GOF, such as targeted therapy with ruxolitinib for STAT1 hyperphosphorylation, immunomodulatory therapy and hematopoietic stem cell transplantation for different self-immune systems, certain curative effects can be obtained. With the understanding of disease mechanisms and the discovery of new clinical phenotypes, this review focuses on the diseases caused by gain-of-function mutations of STAT1, and introduces the clinical manifestations and treatment progress of STAT1-GOF to promote the understanding of such diseases and their future diagnosis, treatment and research works.